VOCATIONAL SCHOOL STUDENTS' PERCEPTIONS REGARDING ENTREPRENEURSHIP PRACTICES, READINESS AND INTEREST - Ramadan, Rian Rizki; Yohana, Corry; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study was conducted with the aim of describing entrepreneurial practices, entrepreneurial readiness, and entrepreneurial interest in vocational high school students based on gender and expertise competencies at Public Vocational High School 22 Jakarta. The research method used in this study is quantitative descriptive method. The respondents used by researchers in this study were grade X students of SMK Negeri 22 Jakarta with an affordable population of 214 students. The sample selection in this study was determined using the Issac & Michael table with an error rate of 5% which found a sample of 135 students. The results of the description analysis of this study found that the variable of entrepreneurial practice had the largest mean value with a score of 4.275 and the lowest value with a score of 4.014. Followed by the variable of entrepreneurial readiness has the highest mean value with a score of 4.370 and the lowest value with a score of 3.986. And the variable of entrepreneurial interest has the largest mean value with a score of 4.341 and the lowest value with a score of 3.957.